Addressing Minoritised Romance Literatures from a Glottopolitical Perspective - Llamedo-Pandiella, Gonzalo (2025)
This paper proposes an approach to the sociodidactics of literatures in minoritised Romance languages from a glottopolitical perspective, in order to highlight the contributions of this critical framework to understanding the literary landscape in vulnerable sociolinguistic contexts. Specifically, these literatures are addressed from two complementary axes that focus on power imbalances: on the one hand, linguistic vulnerability, which explores the development of these literatures in relation to the inequalities inherent to their sociolinguistic context; and, on the other hand, identity vulnerability, which problematises the limitations of the canon and examines the intersectional relationship between these literatures and those of other minoritised voices.